Generation Z Antecedent to Chooses Private Islamic Universities - Fathorrahman, Fathorrahman (Universitas Al-Amien Prenduan, 2024)
This study aims to examine the influence of the image of private Islamic universities, service quality, facilities, and achievement motivation of Generation Z on their intention to choose private Islamic higher education institutions in Indonesia. Considering that Generation Z possesses unique characteristics and a high orientation towards technology, selecting a university presents a specific challenge. The research employs a quantitative survey method with a SEM-PLS approach, involving respondents aged 15-23 years. The results indicate that the image of the university has a small positive influence (p-value 0.023), perceived service quality has a significant positive impact (p-value 0.001), while perceived facility quality shows no significant effect (p-value 0.249). Additionally, achievement motivation displays a strong positive influence (p-value 0.000) on the intention to choose. These findings conclude that private Islamic universities need to focus on enhancing their image and service quality to attract prospective students. This research contributes significantly to the development of promotional strategies for higher education within the competitive Gen Z market. The results are expected to serve as a reference for educational institutions to create better services and images, thereby meeting the needs and expectations of future generations.